2017
DOI: 10.18632/oncotarget.16563
|View full text |Cite
|
Sign up to set email alerts
|

NDV-D90 suppresses growth of gastric cancer and cancer-related vascularization

Abstract: Recent reports suggest promises on using oncolytic Newcastle disease viruses (NDV) to treat different cancers, while the effects of a NDV-D90 strain on gastric cancer remain unknown. Here we showed that NDV-D90 induced gastric cancer cell apoptosis in a dose-dependent manner in 3 gastric cancer cell lines BGC-823, SGC-7901 and MKN-28. Pronounced reduction in cell invasion was detected in NDV-D90-treated BGC-823 and SGC-7901 cells, but not in MKN-28 cells. The increases in cell apoptosis and reduction in cell g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The NDV strain 73T is now under phase II clinical trial by NCI, USA, for the treatment of Melanoma 9 . NDV strains V4UPM, AF2240, D90 were also shown to have oncolytic properties in various cancer cells 1012 . Tumor cells generally have a defective antiviral response, which supports replication of NDV 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The NDV strain 73T is now under phase II clinical trial by NCI, USA, for the treatment of Melanoma 9 . NDV strains V4UPM, AF2240, D90 were also shown to have oncolytic properties in various cancer cells 1012 . Tumor cells generally have a defective antiviral response, which supports replication of NDV 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Both TMZ and NDV induce GBM apoptosis in vitro through AMPK activation, but this AMPK activation is not the only mechanism responsible for the effect of TMZ and NDV 3 , 12 . NDV, as a type of OV, operates via a complex mechanism 1 , 8 , 19 – 23 . Our experiments confirmed that NDV inhibits AKT and activates AMPK when combined with TMZ.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 14 . Moreover, NDV has good anti-tumor potential according to studies investigating other tumor types 4 , 11 , 14 , 15 , 20 , 22 , 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Newcastle disease viruses (NDV)-D90 induce gastric cancer cell apoptosis by stimulation of p38 signalling, suppression of ERK1/2 and Akt signalling, and angiogenesis inhibition. 112 In vivo , orthotopic injection of NDV-D90 impaired tumour growth and induced intratumoural necrosis, and clinical trials of other oncolytic viruses including recombinant vesicular stomatitis virus are underway [ClinicalTrials.gov identifier: NCT02923466].…”
Section: Role Of Combination Of Icpi With Chemotherapy Targeted Thermentioning
confidence: 99%